2012
DOI: 10.1063/1.4757996
|View full text |Cite
|
Sign up to set email alerts
|

Gallium nitride-based light-emitting diodes with embedded air voids grown on Ar-implanted AlN/sapphire substrate

Abstract: GaN-based light-emitting diodes (LEDs) grown on sapphire with ex situ AlN nucleation layer prepared by radio-frequency sputtering were investigated. GaN-based epitaxial layers grown on the Ar-implanted AlN/sapphire (AIAS) substrates exhibited selective growth and subsequent lateral growth due to the difference of lattice constants between the implanted and implantation-free regions. Consequently, air voids over the implanted regions were formed around the GaN/AlN/sapphire interfaces. We proposed the growth mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…For LED chips on LSAT substrates, even when the injection current increases to 100 mA, the light output power still exhibits an upward trend without saturation, indicating excellent electronic properties which are comparable to the conventional GaN-based LEDs grown on sapphire. 52,53 It can be also noted that the light output power for LED on LSAT is some higher than that of LED on sapphire. For example, at an injection current of 20 mA, the light output powers for LEDs on LSAT and sapphire are 4.3 mW and 3.5 mW, respectively, Fig.…”
Section: Journal Of Materials Chemistry C Papermentioning
confidence: 99%
See 2 more Smart Citations
“…For LED chips on LSAT substrates, even when the injection current increases to 100 mA, the light output power still exhibits an upward trend without saturation, indicating excellent electronic properties which are comparable to the conventional GaN-based LEDs grown on sapphire. 52,53 It can be also noted that the light output power for LED on LSAT is some higher than that of LED on sapphire. For example, at an injection current of 20 mA, the light output powers for LEDs on LSAT and sapphire are 4.3 mW and 3.5 mW, respectively, Fig.…”
Section: Journal Of Materials Chemistry C Papermentioning
confidence: 99%
“…This enhancement in light output for the LED on LSAT might be partly attributed to the uniformity of current spreading in the LED on LSAT substrates due to the better crystalline quality of epitaxial layers, which enhances internal quantum efficiency (IQE) and extraction efficiency. 52,54,55 Fig. 10b illustrates the relationship between the injection current (I) and forward voltage (V) for LED chips on both LSAT and sapphire substrates at room temperature.…”
Section: Journal Of Materials Chemistry C Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lai et al reported an ex situ AlN buffer layer deposited by sputter, which yielded an interruption-free GaN epitaxy [28]. To further improve the light extraction efficiency, Sheu et al implanted Ar into a sputtered AlN nucleation layer, and their results showed that the GaN-based epitaxial layer grown on implanted regions has lower growth rates than the implantation-free regions, which eventually form the embedded air voids [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…We attribute the lower forward voltage of the LED chip grown on LiGaO 2 (100) substrate to the lower series resistance in the LED chip on the LiGaO 2 (100) substrate of $7 U compared with that on the c-plane sapphire substrate of $10 U. 4,[37][38][39][40][41][42] Furthermore, the EQE for LED chips on LiGaO 2 (100) and c-plane sapphire substrates were also studied. Fig.…”
mentioning
confidence: 99%